Kinetic energy distribution for the ionization and dissociation process of C2H4 by electron impact. (15th January 2015) - Wang, X; Chen, Z; Wei, B; Hutton, R; Zou, Y
Abstract: The dissociative ionization of ethylene molecules following impact by electrons in the energy range of 20 to 200 eV has been studied with a cold target recoil-ion momentum spectrometer (COLTRIMS). The relative partial cross sections for the ionic fragments C2 Hn + (n=0 3) with respect to C2 H4 + were plotted as a function of the incident energy. By measuring the time of flight and position of the fragment ions, the kinetic energy distribution has been deduced. Taking advantage of the supersonic jet expansion, the thermal motion contributing to the kinetic energy distribution of the recoil-ions was reduced. The average kinetic energy of the recoil ions as a function of the incident electron energy has also been plotted. Furthermore, the average kinetic energy release for the dissociation to C2 H3 + and C2 H2 + were estimated as 0.76 eV and 0.73 eV respectively.